Improving the Compressive Properties of Conveyor Chains in a Tobacco Cutting Machine - علي هترة,; نيرودا بركات ,; يوسف سمير ديب, (Latakia University Journal -Engineering Sciences Series, 2023)
This research aims to improve the pressure properties of the metal link plates used in the conveyor chains of the Hauni tobacco cutting machine in the Tobacco Directorate in Lattakia, in order to reduce the time of breakdowns and maintenance and the resulting costs, and thus improve its service life and reach a good and safe long-term conveyor belt system that meets working conditions required. In this research, the focus was on the breakdown of the plates of the connecting plates of the copper metal conveyor chains and the study of their behavior while working under the influence of the load, and the investigation of the causes of their collapse. The link plate with the increase in loading cycles, as a result of being subjected to periodic variable forces of tension and pressure, causing the emergence of the phenomenon of fatigue, and thus the collapse of conveying chains and very large losses in tobacco and copper connections, which are expensive, and a decrease in productivity. The chemical analysis was carried out on the Foundry-Master device to find out the percentages of the elements included in the composition of the used copper alloy A: Cu -7.85 Ni -24.8 Zn -1.08 Al. The pressure test samples were prepared from the aforementioned alloy according to the standard specifications according to ASTM, and the necessary mechanical tests were performed to find out the pressure resistance on the "UNIVERSAL TESTING MACHINE" model "IBMU4-1000". The effect of alloying elements on the compressive properties of heat-treatable copper alloys was studied, and the new copper alloy B: Cu -11.81 Ni -20 Zn -2 Al was selected and the appropriate mechanical and thermal treatment was applied to it in order to improve the compressive properties. The study was conducted experimentally and the results of the tests showed, through comparison between the results, an improvement in the pressure resistance when using the copper alloy Cu -11.81 Ni -20 Zn -2 Al and the appropriate thermal and mechanical treatments.